Application of UPFC to improve the low-voltage-ride-through capability of DFIG - Alharbi, Y.; Abu-Siada, Ahmed (2015)
In this paper, a new controller approach for unified power flow controller (UPFC) is proposed to improve the low-voltage-ride-through (LVRT) capability of a DFIG-based WECS during voltage sag. The shunt and series converters of the UPFC are controlled using a hysteresis current controller (HCC) and proportional integral controllers (PI), respectively. Detailed simulation is carried out using MATLAB/SIMULINK software to highlight the impact of UPFC in improving the overall system performance during grid fault.